Reactions of p-Nitrophenyloxirane with Amines Containing Fragments with Bicyclic Skeleton - Kas'yan, A. O.; Golodaeva, E. A.; Tsygankov, A. V.; Kas'yan, L. I. (Pleiades Publishing, 2002)
Reactions of p-nitrophenyloxirane with amines containing fragments with bicyclic skeleton of norbornene, norbornane, epoxynorbornane (stereoisomeric exo- and endo-5-aminomethylbicyclo[2.2.1]hept-2-enes, N-benzyl-endo-5-aminomethylbicyclo[2.2.1]hept-2-ene, endo-5-(2-aminoethyl)bicyclo[2.2.1]hept-2-ene, stereoisomeric exo- and endo-2-aminomethylbicyclo[2.2.1]heptanes, 2-(1-aminoethyl)bicyclo[2.2.1]-heptane, exo-5-aminomethyl-exo-2,3-epoxybicyclo[2.2.1]heptane) were investigated. The aminolysis of pnitrophenyloxirane occurred regioselectively according to Krasusky rule as was proved by 1H and 13C NMR data. As shown by 1H and 13C NMR spectroscopy the oxyalkylation product obtained from N-benzyl-endo-5-aminomethylbicyclo[2.2.1]hept-2-ene was composed of two diastereomers originating from the presence of a chiral nitrogen atom in the rear part of the rigid bicyclic skeleton. New products of amino groups transformation in the molecules of hydroxyamines were obtained by reaction with p-methylbenzoyl chloride and p-nitrophenylsulfonyl chloride. Regioselectivity of the attack of electrophilic reagents on the nitrogen in the hydroxyamines was confirmed by IR and 1H NMR spectra of the products. The data on pharmacological activity tests of N-2-hydroxyethyl(p-nitrophenyl)-5-aminomethylbicyclo[2.2.1]hept-2-ene are reported.